Short Review: Cu Catalyst for Autothermal Reforming Methanol for Hydrogen Production - Ho-Shing Wu; Donny Lesmana (Bulletin of Chemical Reaction Engineering & Catalysis, 2012)
Hydrogen is a promising alternative energy sources, hydrogen can be used in fuel cell applications to pro-ducing electrical energy and water as byproduct. Therefore, fuel cell is a simple application and environ-mentally friendly oriented technology. Recent years various methods have been conducted to produce hy-drogen. Those methods are derived from various sources such as methanol, ethanol, gasoline, hydrocarbons. This article presents a brief review a parameter process of that affects in autothermal reforming methanol use Cu-based catalysts for production of hydrogen. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)